2004
DOI: 10.1097/00000542-200410000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Severe Neurological Complications after Central Neuraxial Blockades in Sweden 1990–1999

Abstract: : More complications than expected were found, probably as a result of the comprehensive study design. Half of the complications were retrieved exclusively from administrative files. Complications occur significantly more often after epidural blockade than after spinal blockade, and the complications are different. Obstetric patients carry significantly lower incidence of complications. Osteoporosis is proposed as a previously neglected risk factor. Close surveillance after central neuraxial blockade is mandat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
522
4
52

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 852 publications
(588 citation statements)
references
References 43 publications
10
522
4
52
Order By: Relevance
“…14 A recent large cohort study reported an incidence of this complication in about 1:200,000. 15 Therefore, an ultrasound scan before spinal anesthesia or a combined spinal-epidural technique may reduce the chances of direct cord trauma.…”
Section: Discussionmentioning
confidence: 99%
“…14 A recent large cohort study reported an incidence of this complication in about 1:200,000. 15 Therefore, an ultrasound scan before spinal anesthesia or a combined spinal-epidural technique may reduce the chances of direct cord trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of neuraxial anesthesia over general anesthesia, it has a theoretical risk for central nervous system (CNS) infections that historically have led to its relative contraindication in patients with systemic or localized infections [22]. This is attributable to the possibility that subarachnoid or dural puncture can spread infection to the epidural or intrathecal space in patients with a systemic infection [27].…”
Section: Introductionmentioning
confidence: 99%
“…Individual cases of these CNS infections have been reported [1,13]; however, the limited and at times conflicting data available do not provide a convincing argument against the use of neuraxial anesthesia in patients with infection. In a retrospective series in Sweden involving 1,260,000 spinal and 450,000 epidural anesthetics performed during a decade, Moen et al [22] reported epidural abscess in 13 patients and meningitis in 29. By contrast, in a multicenter prospective study involving 30,413 epidural and 40,640 spinal anesthetics, no infectious complications were reported [2].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20]. Die Analyse großer Patientenkollektive zeigte die tatsächlichen Risiken bei neuroaxialen Blockaden, insbesondere bei der Anwendung von Epiduralkathetern in bestimmten Patientenkollektiven [21][22][23]. So existiert für die Regionalanästhesie im Rahmen der Knieendoprothetik mit der Blockade peripherer Nerven heute eine im Vergleich zur Epiduralanästhesie gleich wirksame und sichere Alternative [24].…”
Section: Neue Optionen Durch Faszienblockadenunclassified